2016
DOI: 10.1016/j.neuroscience.2016.06.043
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine-induced acute hyperactivity is mediated by dopaminergic system in a sexually dimorphic manner

Abstract: Short-term exposure to nicotine induces positive effects in mice, monkeys and humans, including mild euphoria, hyperactivity, and enhanced cognition. However, the underlying neural basis and molecular mechanisms for these effects remain poorly understood. Here, using a video recording system, we find that acute nicotine administration induces locomotor hyperactivity in Drosophila, similar to observations made in higher model organisms. Suppressing dopaminergic neurons or down-regulating dopamine 1-like recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Determining how sexually isomorphic circuits are modified to produce sexually dimorphic behaviors is a complex endeavor. Even shared systems for such basic activities like movement are modified in a sex-specific way in species ranging from C. elegans and Drosophila to humans, and this modification is dependent on the sex of the nervous system, not just differences in body morphology ( Mowrey et al 2014 ; Smith and Mittendorfer 2016 ; Zhang et al 2016 ). However, little is known about the underlying mechanisms driving the sexual dimorphism.…”
Section: Discussionmentioning
confidence: 99%
“…Determining how sexually isomorphic circuits are modified to produce sexually dimorphic behaviors is a complex endeavor. Even shared systems for such basic activities like movement are modified in a sex-specific way in species ranging from C. elegans and Drosophila to humans, and this modification is dependent on the sex of the nervous system, not just differences in body morphology ( Mowrey et al 2014 ; Smith and Mittendorfer 2016 ; Zhang et al 2016 ). However, little is known about the underlying mechanisms driving the sexual dimorphism.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Zhang et al showed that dopamine also mediates the chronic nicotine exposure-induced locomotor hyperactivity in adult flies described by Ren et al [42,69]. In mammals and Drosophila , alpha7 receptors have been associated to biogenic amine release [41,63].…”
Section: Discussionmentioning
confidence: 99%
“…Drosophila strains with mutations of Dα1, Dα2, or Dβ2 nAChR subunits are highly resistant to the neonicotinoids nitenpyram and imidacloprid (Perry et al, 2008). The behavioral effects of nicotine on Drosophila are regulated by dopamine (Bainton et al, 2000), and Dβ1 subunit in dopaminergic neurons play a role in acute locomotor hyperactivity caused by nicotine in male Drosophila (Zhang et al, 2016). Therefore, understanding how nAChR control dopamine release is critical for understanding the effects of neonicotinoids.…”
Section: Introductionmentioning
confidence: 99%